SecureChild - Children Tracking Android Application (International Journal of Scientific Research and Management (IJSRM), 2015)
Android operating system is at the top in market because of its features like portability, platform independence, and low memory consumption. As android operating System is used in mobile phones, tablets and laptops it has covered more than 80% of the market. Now everyone is using android phone. As android is an open source operating system many developers are developing various applications every day, Millions of applications are available for use free of cost. These applications are helpful for Ticket booking, Banking services, Online shopping, Tracking our family members etc. The SecureChild Application is designed for School and Parent to track the children while they are travelling through School Van. The days are Gone when one of the two parents will sit at home to take care of the children and one earns. Now time has come for both the parents to work; in such scenario the security of children is very important. The numbers of users have Android phone equipped with Global Positioning System which can be used efficiently for security and protection purpose. This Application is mainly developed for toddler going to school to make sure that at what exact time child has reached school and at what time he/she left school. Also gives the van location and information about van drivers and Babysitter which will be in van to take care of toddlers. This also gives the expected time of the van while pick up and drop. This “SecureChild” is a multipurpose children safety application which will work on android platform.